Time banks vs household production theory and threats to the fiscal security of the state - Stępnicka, Nina; Wiączek, Paulina (Banki czasu a teoria produkcji domowej i zagrożenia bezpieczeństwa fiskalnego państwa, 2019)
The aim of the article is to demonstrate that time banks are an example of one of the many models of a cooperation economy, including a shared way of life. We can place them in the category of so-called household production. The research on this issue was conducted by American economist Hazel Kyrk (1886-1957), a founder of the so-called home economics. According to Kyrk’s theory, time banks are a part of household production, which is free of charge and enables to use resources of households in a more efficient way. The authors used the historical method and the method of the critical analysis of literature
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 127-135
Keywords: time banks; financial security; cooperation economy; household production; security threats; banki czasu; bezpieczeństwo finansowe; gospodarka współpracy; produkcja gospodarstw domowych; zagrożenia bezpieczeństwa